Issues of Administrative Responsibility for the Trade of Alcohol Products - Vasilii A. Bondarenko; Nikolai M. Zhdanov (Сибирское юридическое обозрение, 2017)
The article deals with the analysis of some provisions of the legislation governing alcohol trade and the practice of implementing administrative responsibility for its violations, proposals are made to improve law enforcement activities in this area. The Authors give some recommendations for the improvement of law enforcement activity in the field.